Prevalence of common mental health disorders in adults who are high or costly users of healthcare services: protocol for a systematic review and meta-analysis - Ferozkhan Jadhakhan; Oana C Lindner; Amy Blakemore; Elspeth Guthrie (BMJ Open)
Introduction In all healthcare settings, a small proportion of patients account for a large level of healthcare use and associated high healthcare costs. Depression and anxiety are common co-morbidities in patients who are high users of care. The aims of this systematic review are to: (1) estimate the prevalence of anxiety/depression in adults who are high users of general physical healthcare services and/or who accrue high healthcare costs (2) estimate the magnitude of healthcare use associated with the presence of anxiety/depression.Methods and analysis This review will include any studies where patients are high users of primary, secondary or emergency healthcare services and/or accrue high healthcare costs. This is the first systematic review to focus on patients who are over the age of 18, whose degree of anxiety/depression has been evaluated with a standardised questionnaire or by a clinical interview generating a diagnosis according to international diagnostic criteria. The review will include eligible studies indexed in Medline, PsychINFO, Embase, Cumulative Index to Nursing and Allied Health Literature, Prospective Register of Systematic Reviews, Cochrane Library from inception to 1 April 2019. We will estimate the prevalence of anxiety/depression in these populations and the magnitude of use associated with anxiety/depression across various general physical healthcare settings. We will provide a narrative description of findings and factors that may influence them. A meta-analysis may be pursued if the degree of heterogeneity across studies is acceptable.Ethics and dissemination This systematic review will use data from existing studies, hence no ethical approvals are required. Findings will be disseminated in a peer-reviewed publication and at relevant academic meetings.PROSPERO registration number PROSPERO CRD42018102628.